A Phonological Study of Child Utterances at the Age of Two - Umayya Idrees Younis (PROSPECTIVE RESEARCHES, 2023)
This study deals with some phonological processes used by children speaking Mosuli Arabic at the age of two. These are: consonant harmony, metathesis substitution, cluster reduction, weak syllable deletion and reduplication. Children make these processes in order to have easy pronunciation. The study has shown that consonant harmony occurs in voicing, place of articulation, manner of articulation and tafxim. Substitution frequently occurs at the age of two and continues till the age of six. Metathesis also appears in a few number of words at the age of two and increases between the third and forth years. Reduplication starts with the first attempts of the child to speak and it gradually increases until it could hardly be found except in few words. To reduce consonant cluster, the child deletes the difficult consonant quite similarly as what he does when he delete the difficult syllable in polysyllabic words.